2022
DOI: 10.1101/2022.06.06.494921
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nirmatrelvir Resistant SARS-CoV-2 Variants with High Fitness in Vitro

Abstract: The oral protease inhibitor nirmatrelvir is expected to play a pivotal role for prevention of severe cases of coronavirus disease 2019 (COVID-19). To facilitate monitoring of potentially emerging resistance, we studied severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) escape from nirmatrelvir. Resistant variants selected in cell culture harbored different combinations of substitutions in the SARS-CoV-2 main protease (Mpro). Reverse genetic studies in a homologous infectious cell culture system revea… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
49
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(63 citation statements)
references
References 40 publications
(42 reference statements)
11
49
1
Order By: Relevance
“…E166H had reduced enzymatic activity (17.5-fold lower in k cat /K m value) and showed drug resistance (368.7-fold increase in IC 50 ). In parallel to our study, two preprints reported nirmatrelvir resistant M pro mutants identified from serial viral passage experiments in cell culture ( 13, 14 ).…”
Section: Identification Of Sars-cov-2 Mpro Mutants From Gisaid Sequen...supporting
confidence: 66%
See 1 more Smart Citation
“…E166H had reduced enzymatic activity (17.5-fold lower in k cat /K m value) and showed drug resistance (368.7-fold increase in IC 50 ). In parallel to our study, two preprints reported nirmatrelvir resistant M pro mutants identified from serial viral passage experiments in cell culture ( 13, 14 ).…”
Section: Identification Of Sars-cov-2 Mpro Mutants From Gisaid Sequen...supporting
confidence: 66%
“…Although the results reassure that the efficacy of nirmatrelvir is not compromised by the current dominant SARS-CoV-2 variants, drug resistance to nirmatrelvir is anticipated given the experience from the clinic use of HIV and HCV protease inhibitors (11,12). Several studies have been conducted to evolve or predict the nirmatrelvir resistant M pro mutants (13)(14)(15)(16).…”
Section: Identification Of Sars-cov-2 M Pro Mutants From Gisaid Seque...mentioning
confidence: 99%
“…1 ) and Huh7-ACE2 cells ( Fig. 2 ), multiple lineages with non- overlapping mutations evolved under increasing drug pressure, consistent with what has been seen in similar small-scale studies 24,25,34,35 . Conducting selection at scale, however, revealed that there are multiple mutational pathways to nirmatrelvir resistance but with several common trajectories preferred ( Figs.…”
Section: Discussionsupporting
confidence: 85%
“…Using this assay, we found that compared to wild-type, the E166R mutation conferred strong nirmatrelvir resistance ( K i > 1000-fold). As the E166 site appears to be a hot spot for drug resistance from in vitro viral evolution experiments 13,14 , we solved the structures of two substitution mutants M pro E166N and M pro E166R, revealing how E166 mutations may compromise activity versus drug resistance, respectively. Our results demonstrate the yeast system can be a reliable tool to determine the activity and drug responses of M pro mutants.…”
Section: Introductionmentioning
confidence: 99%